2022
DOI: 10.3390/ijerph192214900
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Intraoral Ultrasound for Preoperative Assessment of Depth of Invasion for Early Tongue Squamous Cell Carcinoma: Radiological–Pathological Correlations

Abstract: The eighth edition of the TNM classification officially introduced “depth of invasion” (DOI) as a criterion for determining the T stage in tongue squamous cell carcinoma. The DOI is a well-known independent risk factor for nodal metastases. In fact, several experts strongly suggest elective neck dissection for tongue cancer with a DOI > 4 mm due to the high risk of early and occult nodal metastases. Imaging plays a pivotal role in preoperative assessments of the DOI and, hence, in planning the surgical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The majority of the studies included in the current scoping review demonstrated a reliable potential of intraoral ultrasound to more efficiently estimate depth of invasion and tumor thickness pre-operatively, demonstrating lower overestimations than CT and MRI, which are more strongly affected by peritumoral edema and reactive inflammation. 11,13,[16][17][18][19] Moreover, the occurrence of metal artifacts is frequently reported as an important limitation of CT, which precludes detailed tongue cancer analyses in a large number of patients that often carry amalgam dental restorations. 6,13 It is known that the higher the depth of invasion of tongue cancer, the higher the frequency of metastases to the cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies included in the current scoping review demonstrated a reliable potential of intraoral ultrasound to more efficiently estimate depth of invasion and tumor thickness pre-operatively, demonstrating lower overestimations than CT and MRI, which are more strongly affected by peritumoral edema and reactive inflammation. 11,13,[16][17][18][19] Moreover, the occurrence of metal artifacts is frequently reported as an important limitation of CT, which precludes detailed tongue cancer analyses in a large number of patients that often carry amalgam dental restorations. 6,13 It is known that the higher the depth of invasion of tongue cancer, the higher the frequency of metastases to the cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the usefulness of intraoral ultrasonography in the evaluation of tongue cancer 5–11 . Lesion length, thickness, depth of invasion, and margins are reported factors associated with late cervical lymph node metastasis, and intraoral ultrasonographic images may contain features related to tongue cancer prognosis 5,7,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the usefulness of intraoral ultrasonography in the evaluation of tongue cancer. [5][6][7][8][9][10][11] Lesion length, thickness, depth of invasion, and margins are reported factors associated with late cervical lymph node metastasis, and intraoral ultrasonographic images may contain features related to tongue cancer prognosis. 5,7,11 Although various studies have reported cervical lymph node metastasis in patients with tongue cancer, insufficient evidence is available to determine whether prophylactic dissection should be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between intraoral ultrasonographic images and late cervical lymph node metastasis has been shown 7–10 . This technique has also been used in measuring the depth of tongue cancer 11–13 . However, few studies have reported on the examination of common submucosal intraoral benign lesions, such as hemangiomas, irritation fibromas, mucous cysts, lipomas, and pleomorphic adenomas, using ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] This technique has also been used in measuring the depth of tongue cancer. [11][12][13] However, few studies have reported on the examination of common submucosal intraoral benign lesions, such as hemangiomas, irritation fibromas, mucous cysts, lipomas, and pleomorphic adenomas, using ultrasonography. We aimed to investigate the features of benign mass lesions in the submucosal epithelium of the oral cavity and to propose a differential diagnosis for each lesion.…”
Section: Introductionmentioning
confidence: 99%